From “Serum Sickness” to “Xenosialitis”: Past, Present, and Future Significance of the Non-human Sialic Acid Neu5Gc - Dhar, Chirag; Sasmal, Aniruddha; Varki, Ajit (Frontiers in Immunology, 2019)
The description of “serum sickness” more than a century ago in humans transfused with animal sera eventually led to the identification of a class of human antibodies directed against glycans bearing the common mammalian sialic acid N-Glycolylneuraminic acid (Neu5Gc), hereafter called “Neu5Gc-glycans”. The detection of such glycans in malignant and fetal human tissues first raised the possibility that it was an oncofetal antigen. However, “serum sickness” antibodies were also noted in various human disease states. These findings spurred further research on Neu5Gc, and the discovery that it is not synthesized in the human body due to a human-lineage specific genetic mutation in the enzyme CMAH. However, with more sensitive techniques Neu5Gc-glycans were detected in smaller quantities on certain human cell types, particularly epithelia and endothelia. The likely explanation is the metabolic incorporation of Neu5Gc from dietary sources, especially red meat of mammalian origin. This incorporated Neu5Gc on glycans serves as the first example of a “xeno-autoantigen” to which varying levels of “xeno-autoantibodies” are present in all humans. The resulting chronic inflammation or “xenosialitis” may have important implications in human health and disease, especially in diseases known to be aggravated by consumption of red meat. In this review, we will cover the early history of the discovery of “serum sickness” antibodies, the subsequent recognition that they were directed against Neu5Gc-glycans, the discovery of the genetic defect eliminating Neu5Gc production in humans, and the subsequent recognition that this was not an oncofetal antigen but the first example of a “xeno-autoantigen”. Further, we will present comments about implications for disease risks associated with red meat consumption such as cancer and atherosclerosis. We will also cover the potential utility of these anti-Neu5Gc-glycan antibodies in onco-immunotherapy and provide some suggestions and perspectives for the future. Other reviews in this issue cover many other aspects of this unusual pathological process, for which there appears to be no other described precedent.